MALAY PROVERBS VISUAL CULTURE: TRENDS AND PATTERNS THROUGH BIBLIOMETRIC ANALYSIS - Siti Nabilah Yusuf; Neesa Ameera Mohamed Salim; Syahrini Shawalludin; Azhar Abd Jamil; Nurul ‘Ayn Sayuti; Mohd Nor Shahizan Ali; Loh Yoke Ling (Jurnal Gendang Alam (GA), 2023)
Proverbs and folklore shape civilization and mankind over time. A non-tangible national art and cultural heritage, Malay proverbs carry the wisdom from the elder generation to their predecessors by defining a specific civilization. Sanskrit proverbs and Malay proverbs have some similarities. Young people use graphic digital media to consume, entertain, and interact. Future scholars can utilise the study to learn more about the field’s current state. This study used Bibliometric Analysis to examine the relationship between visual graphics, digital media, and Malay Proverb from 2000 to 2023. Scopus and Lens.org provided 178 papers for study. To add context, this document includes the year, writer, keyword, and country. This study only accepts peer-reviewed journal articles, conference papers, and books. Publication year, authors, journal/conference/book titles, abstracts, keywords, and citations will be extracted. For analysis, Scopus and lens.org provided publication year, journal/conference/book title, authors, keywords abstract, and citation information. The study found that Malay Proverb research has consistently expanded, peaking at 20 articles in 2020. The trend and development in research on Malay Proverb and graphic digital media from 2000 to 2023 shows the study of Malay Proverb as a medium of communication and expression and its integration with current graphic digital media.